Investigation of the acoustic field distribution in piezoelectric transducers by the bragg diffraction method - KLESZCZEWSKI, Zygmunt (Archives of Acoustics, 1979)
In the paper the possibility of using the light, diffracted by acoustic waves, for the investigation of the distribution of acoustic fields in solids is presented, and the results obtained are described. Quartz and LiIO3 transducers with a fundamental frequency of 200-400 MHz were the sources of a longitudinal acoustic wave. The transducer length was several mm, and the transducer width was about 1 mm. Fused and crystalline quartzes were used as media. The acoustic field was probed with a narrow laser beam, and the angular distribution of the diffracted light intensity was measured. The experimental results obtained were compared with theoretical calculations.